HARNESSING THE POWER OF ARTIFICIAL NEURAL NETWORKS FOR ADVANCED STATISTICAL ANALYSIS - Mukhitdinova Munavvarhon Khayotovna (American Journals, 2023)
This article provides a comprehensive review of the use of Artificial Neural Networks (ANNs) in advanced statistical analysis. Due to the growing complexity and scale of data, traditional statistical methods often do not provide accurate and reliable analysis. ANNs, with their inherent ability to model non-linear relationships and process multidimensional data, are an effective solution. Methodological developments, practical applications and problems arising from the use of ANN for statistical research are analyzed.
Keywords: Artificial Neural Networks, Statistical Analysis, Literature Review, Methodological Developments, Practical Applications, Future Directions.